Effective crisis communication and its role in spreading awareness and addressing the Corona crisis - a field study of the regional hospital of the state of Souk Ahras - - menmani, mobarka (Journal of Social Sciences and Humanities, 2024)
As soon as the media and communication rang the alarm, declaring that all of humanity is facing a crisis that may affect all segments of society and may lead to great human losses, this news caused the concerned authorities to be confused, as the medical staff found themselves facing several options and between life and death. Raising the level of communication between doctors and nurses and between patients to know the peculiarities of the epidemic, and this required the necessary foundations of awareness, and developed hospitals rushed to develop an external and internal communication plan to get out of the crisis, and in this regard our field study came to find out whether the regional hospital of the state Souk Ahras pays attention to the communication aspect during the Covid 19 crisis, as well as an attempt to find out whether this institution has developed an effective communication plan or strategy to contain the situation. Souk Ahras State to answer the following problem: Does effective communication contribute to addressing the Corona crisis in the regional hospital of Souk Ahras State? The study concluded with a number of results, the most important of which is that the regional hospital relies on communication activity in the management of the Corona crisis by a large percentage, despite the absence of communication culture, and it did not rely on a communication strategy to address the crisis, due to the lack of specialists in communication.